2000
DOI: 10.1126/science.287.5461.2220
|View full text |Cite
|
Sign up to set email alerts
|

From Sequence to Chromosome: The Tip of the X Chromosome of D. melanogaster

Abstract: One of the rewards of having a Drosophila melanogaster whole-genome sequence will be the potential to understand the molecular bases for structural features of chromosomes that have been a long-standing puzzle. Analysis of 2.6 megabases of sequence from the tip of the X chromosome of Drosophila identifies 273 genes. Cloned DNAs from the characteristic bulbous structure at the tip of the X chromosome in the region of the broad complex display an unusual pattern of in situ hybridization. Sequence analysis reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 26 publications
0
19
0
Order By: Relevance
“…Primers for the most distal of the amplicons (numbered 1-4) were designed using the X chromosome sequence from Canton-S, originally part of the Drosophila Sequencing Project (accession no. AL031884) and sequenced by the European Drosophila Genome Project (Benos et al 2000). As mentioned above, Canton-S possesses a structurally distinct X subtelomere from the reference strain, y; cn bw sp, in that it includes a repetitive region of the subtelomere containing the canonical X TAS, characterized by Karpen and Spradling (1992;see Figure 2).…”
Section: Methodsmentioning
confidence: 99%
“…Primers for the most distal of the amplicons (numbered 1-4) were designed using the X chromosome sequence from Canton-S, originally part of the Drosophila Sequencing Project (accession no. AL031884) and sequenced by the European Drosophila Genome Project (Benos et al 2000). As mentioned above, Canton-S possesses a structurally distinct X subtelomere from the reference strain, y; cn bw sp, in that it includes a repetitive region of the subtelomere containing the canonical X TAS, characterized by Karpen and Spradling (1992;see Figure 2).…”
Section: Methodsmentioning
confidence: 99%
“…The BAC clones (Benos et al 2000) and cosmids clones (Siden-Kiamos et al 1990) are available from http://www.geneservice.co.uk. Cosmid and BAC 96-well IDs and accession numbers are as follows: 30B7 (AL021107), 137E7 (AL021108), 131F2 (AL024456), 63B12 (AL021106), 86E4 (AL021086), 39E1 (AL009191), BACH0.26e3 (AL035245).…”
Section: Clonesmentioning
confidence: 99%
“…Cosmid and BAC clones used by the European Drosophila Genome Project (Benos et al 2000) were obtained from the participant laboratories or from the Human Genome Mapping Project (HGMP) resource center. The BAC clones (Benos et al 2000) and cosmids clones (Siden-Kiamos et al 1990) are available from http://www.geneservice.co.uk.…”
Section: Clonesmentioning
confidence: 99%
“…Amino acid sequences of the genes in divisions 1-3 of chromosome X of D. melanogaster can be obtained by anonymous FTP from ftp://ftp.ebi.ac.uk/pub/databases/edgp/misc/ ashburner/EG_genes.991229.pep.fa.gz (Benos et al 2000(Benos et al , 2001, whereas amino acid sequences of the genes identified in the Adh region are found in http://www.fruit fly.org/ sequences/aa_Adh.dros (Ashburner et al 1999). Amino acid sequences of all genes identified through the whole genome sequence (release 1.0) are available at http://www.fruitfly.org/ sequence/dlMfasta.html (Adams et al 2000).…”
Section: Source Of Sequence Datamentioning
confidence: 99%